2014
DOI: 10.1016/j.nut.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte saturated fatty acids and systemic inflammation in adults

Abstract: Objective The role of saturated fatty acids (SFAs) in chronic disease remains controversial; inflammation is one pathway by which SFAs influence the risk of chronic disease. We aim to investigate the associations between red blood cell (RBC) phospholipid SFAs and systemic inflammation. Methods As part of a randomized controlled trial, we measured RBC phospholipid FA composition among 55 generally healthy adults twice at three-month intervals. We estimated associations of RBC total SFAs and two major SFA subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 47 publications
0
24
0
5
Order By: Relevance
“…11 In addition, the even-numbered SFA and MUFA were found to be correlated with composite inflammation measures 12 and may thus influence risk of NHL via pro-inflammatory mechanisms. 12 However, oddnumbered SFA [e.g., pentadecanoic acid (15:0) and heptadecanoic acid (17:0)] primarily reflect dairy fat consumption and not endogenous synthesis. 13 A meta-analysis suggested a positive association of dairy product consumption with risk of NHL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In addition, the even-numbered SFA and MUFA were found to be correlated with composite inflammation measures 12 and may thus influence risk of NHL via pro-inflammatory mechanisms. 12 However, oddnumbered SFA [e.g., pentadecanoic acid (15:0) and heptadecanoic acid (17:0)] primarily reflect dairy fat consumption and not endogenous synthesis. 13 A meta-analysis suggested a positive association of dairy product consumption with risk of NHL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in vivo study treatment with ST1326, an inhibitor of carnitine‐palmitoyl transferase 1A, prevented lymphomagenesis in mice by reducing the availability of a fundamental substrate for de novo lipogenesis . In addition, the even‐numbered SFA and MUFA were found to be correlated with composite inflammation measures and may thus influence risk of NHL via pro‐inflammatory mechanisms . However, odd‐numbered SFA [e.g., pentadecanoic acid (15:0) and heptadecanoic acid (17:0)] primarily reflect dairy fat consumption and not endogenous synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…Higher intakes of saturated fat were positively associated with CRP, IL-6, and ICAM-1 (73). In another study, erythrocyte fatty acid composition in 55 healthy adults was compared to serum CRP and IL-6 concentrations (74). In multivariate models, total saturated fatty acids were modestly associated with IL-6 ( P =0.05) and CRP ( P =0.06), but palmitic and stearic acids, specifically, were significantly associated with IL-6 ( P =0.006) and CRP ( P =0.04), respectively (74).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, erythrocyte fatty acid composition in 55 healthy adults was compared to serum CRP and IL-6 concentrations (74). In multivariate models, total saturated fatty acids were modestly associated with IL-6 ( P =0.05) and CRP ( P =0.06), but palmitic and stearic acids, specifically, were significantly associated with IL-6 ( P =0.006) and CRP ( P =0.04), respectively (74). Finally, a population-based dietary inflammatory index developed by Shivappa, et al,(51) which scored the inflammatory potential for a variety of dietary components based on extensive primary literature evaluating dietary associations with a panel of inflammation markers (CRP, IL-1β, IL-4, IL-6, IL-10, and TNF-α), found an overall positive association of saturated fat and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In immune cells, fatty acids are used either as fuel for cellular metabolism through oxidation or as major components of membranes for cells or organelles such as the endoplasmic reticulum (ER) or Golgi body . Studies have also identified roles of fatty acids in the immune response and inflammation, that is saturated fatty acids promote inflammation, whereas polyunsaturated fatty acids exert anti‐inflammatory effects . Fatty acid metabolism, including FAS in immune cells, is illustrated in Figure .…”
Section: Fas In Immune Cellsmentioning
confidence: 99%